Guaranteeing the Rights of Children and Women Post-Divorce: A Comparative Study Between Indonesia and Malaysia - Musaddad, Endad; Ishom, Muhammad; Mat Hussin, Mohd Norhusairi; Jambunanda, Ahmad Jamaludin (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
The enforcement of court decisions regarding custody (hadanah) and alimony (nafkah) for children and ex-wives post-divorce is frequently inadequate, with many husbands failing to comply. Although decisions based on legal provisions (rechtsspraack naar wetboeken) should be effective according to the principle of the Effectiveness of Law, numerous children and women in Indonesia suffer from the ineffective execution of judges' rulings in alimony and custody cases. Ensuring the rights of children and women after divorce can be improved through proper implementation of laws in a preventive, curative, and supportive manner. In Indonesia, the E-Mosi Caper application has been developed in Bengkulu Province, in collaboration with the PTA Bengkulu and local government, to enhance the effectiveness of laws concerning custody and alimony. This application could serve as a model for other regions. In contrast, Malaysia has established a Family Support Division (BSK) tasked with overseeing maintenance payments to support children and ex-wives after divorce. This study employs a comparative legal method to examine the frameworks for ensuring the rights of children and women post-divorce in both countries. The findings aim to highlight the effectiveness of the existing systems and after recommendations for improving law enforcement and protecting post-divorce rights.